The Implementation of Classpoint in Learning English: A Case Study - Oktadela, Resy; Shalawati, Shalawati; Hadiyanti, Putri Octa; Elida, Yusti; Ismail, Syofianis (Universitas Pahlawan Tuanku Tambusai, 2024)
The use of Information and Communication Technology (ICT) in instructional and learning activities significantly impacts enhancing the quality of education, especially in the current era of the industrial revolution 4.0. Classpoint is a learning platform that facilitates IT-based educational activities. This study aims to assess the implementation of Classpoints in teaching English to fifth graders at SD IT Imam Syafei Pekanbaru during the 2023/2024 academic year. The research adopts a qualitative approach, specifically case study research. Data collection methods include observation and interviews. The techniques used for data analysis are data reduction, data presentation, and conclusion drawing. To ensure data validity, data triangulation, method triangulation, and source triangulation were employed. The research findings indicate that the implementation of Classpoint at SD IT Imam Syafei Pekanbaru is highly effective for teaching English.